The O. Henry Awards prize stories, 2006 - Furman, Laura (New York : Anchor Books, 2006)
"A radiant reflection of contemporary fiction at its best, The O. Henry Prize Stories 2006 features stories from locales as diverse as Russia, Zimbabwe, and the rural American South. Series editor Laura Furman considered thousands of stories in hundreds of literary magazines before selecting the winners, which are accompanied here by short essays from each of the three eminent jurors on his or her favorite story, as well as observations from all twenty prize winners on what inspired them. Ranging in tone from arch humor to self-deluding obsessiveness to fairy-tale ingenuousness, these stories are a treasury of potential classics."--The publisher.
Old boys, old girls / Edward P. Jones -- You go when you can no longer stay / Jackie Kay -- Mule killers / Lydia Peelle -- The broad estates of death / Paul Fox -- The pelvis series / Neela Vaswani -- conceived / David Lawrence Morse -- The dressmaker's child / William Trevor -- Disquisition on tears / Stephanie Reents -- Sault Ste. Marie / David Means -- Unction / Karen Brown -- '80s Lilies / Terese Svoboda -- Passion / Alice Munro -- The center of the world / George Makana Clark -- Wolves / Susan Fromberg Schaeffer -- Girls I know / Douglas Trevor -- The plague of doves / Louise Erdrich -- Famine / Xu Xi -- Puffed rice and meatballs / Lara Vapnyar -- Letters in the snow-for kind strangers and unborn children-for the ones lost and most beloved / Melanie Rae Thon -- Window / Deborah Eisenberg -- Reading the O. Henry Prize stories 2006 -- Writing the O. Henry Prize stories 2006.
"An Anchor Books original"--Title page verso.
O. Henry Memorial Award, 2006.
Keywords: American fiction -- 20th century; Short stories, American; United States -- Social life and customs -- Fiction